Pengalaman Guru dalam Menerapkan Pembelajaran Seni Rupa untuk Anak Kelas I di MIN 2 Palangka Raya - Dinna Aulia; Istiyati Mahmudah (CV. Aksara Global, 2024)
Education is the process of transferring knowledge, skills and values ​​to shape individual development, both formally in educational institutions and informally. The goal is to improve physical, intellectual, emotional and social abilities so that individuals can play an active role in society. This research aims to explore teaching experiences and approaches in developing students' creativity and artistic talents. The research method used is a case study through in-depth interviews and direct observation in class. The research results found that having various positive experiences in teaching fine arts in grade 1 has influenced his teaching approach. By implementing various effective strategies in overcoming teaching obstacles and adapting methods to student characteristics. The main activities implemented are drawing and coloring projects to stimulate student creativity and expression. One significant approach is to involve students' parents in developing their artistic talents. This research reveals that the approach is very useful in motivating students and creating a pleasant learning climate. This has a positive impact in improving the quality of fine arts learning in grade 1 SD/MI. It is hoped that this research can become a reference in enriching the art learning experience at the initial level of basic education.